PREVALENCE OF FEMALE INFERTILITY AMONG URBAN AND RURAL POPULATION IN BURYAT REPUBLIC - DARZHAEV, Z.Yu; ATALYAN, A.V.; RINCHINDORZHIYEVA, M.P.; SUTURINA, L.V. (Fundamental and Clinical Medicine, 2017)
Aim. To determine the prevalence of female infertility among the urban and rural population of Buryat Republic. Materials and Methods. We recruited 2,038 women of reproductive age: 1,495 women living in Ulan-Ude (826 Caucasians and 669 Asians) and 543 women from the rural areas (302 Caucasians and 241 Asians). We used a questionnaire (Filippov, 1999) which eventually distributed the study participants into five categories: fertile, probably fertile, with primary infertility, with secondary infertility, and with unknown fertility. Results. The prevalence of female infertility in Buryat Republic was 22.82% (95% CI: 21.05-24.69), with no significant differences among Caucasians and Asians (21.9%, 95% CI: 19.58-24.41 and 23.96%, 95% CI: 21.29-26.84, respectively, p = 0.3). Overall, secondary infertility was more common in comparison with the primary one; furthermore, the prevalence of secondary infertility was significantly higher in Asians compared to Caucasians. In the urban population, the prevalence of female infertility was 19.67% (95% CI: 17.73-21.76), without significant differences among Caucasians and Asians. The prevalence of secondary infertility in urban population significantly exceeded those of primary infertility regardless of the ethnicity. Among the rural population, the prevalence of female infertility was 31.49% (95% CI: 27.72-35.52), with no significant differences between Caucasians and Asians. Notably, Caucasian females living in the rural areas had higher prevalence of primary infertility compared to the secondary infertility. Female infertility in the rural population was considerably higher than in urban population (31.49% and 19.67%, p < 0.001), with a significantly higher frequency of primary infertility in rural women (19.15% and 5.35%, p < 0.001). Conclusion. The prevalence of female infertility in the Buryat Republic is around 23% and depends on the area of living rather than on the ethnicity.